Spaces of Scientific Knowledge - Stehr, Nico (Zagadnienia Naukoznawstwa, 2024)
Perhaps the first and most pertinent observation that comes to mind when considering knowledge spaces is that scientific knowledge knows no boundaries. However, it would be naive to assume that knowledge flow freely and without cost within and across borders. Indeed, distance can be largerly irrelevant among influences on the cognitive outcomes of scientific collaboration. The nature of the social and cognitive ties between scientists has a greater influence.